Niemann-Pick Type C1 I1061T Mutant Encodes a Functional Protein That Is Selected for Endoplasmic Reticulum-associated Degradation Due to Protein Misfolding - Gelsthorpe, Mark E. (American Society for Biochemistry and Molecular Biology, 2008)
Over 200 disease-causing mutations have been identified in the NPC1 gene. The most prevalent mutation, NPC1(I1061T), is predicted to lie within the cysteine-rich luminal domain and is associated with the classic juvenile-onset phenotype of Niemann-Pick type C disease. To gain insight into the molecular mechanism by which the NPC1(I1061T) mutation causes disease, we examined expression of the mutant protein in human fibroblasts homozygous for the NPC1(I1061T) mutation. Despite similar NPC1 mRNA levels between wild type and NPC1(I1061T) fibroblasts, NPC1 protein levels are decreased by 85% in NPC1(I1061T) cells. Metabolic labeling studies demonstrate that unlike wild type protein, which undergoes a glycosylation pattern shift from Endo H-sensitive to Endo H-resistant species, NPC1(I1061T) protein remains almost exclusively Endo H-sensitive and exhibits a reduced half-life (t(½) 6.5 h) versus wild type Endo H-resistant species (t(½) 42 h). Treatment with chemical chaperones, growth at permissive temperature, or inhibition of proteasomal degradation increases NPC1(I1061T) protein levels, indicating that the mutant protein is likely targeted for endoplasmic reticulum-associated degradation (ERAD) due to protein misfolding. Overexpression of NPC1(I1061T) in NPC1-deficient cells results in late endosomal localization of the mutant protein and complementation of the NPC mutant phenotype, likely due to a small proportion of the nascent NPC1(I1061T) protein that is able to fold correctly and escape the endoplasmic reticulum quality control checkpoints. Our findings provide the first description of an endoplasmic reticulum trafficking defect as a mechanism for human NPC disease, shedding light on the mechanism by which the NPC1(I1061T) mutation causes disease and suggesting novel approaches to treat NPC disease caused by the NPC1(I1061T) mutation.